(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: Adequate closure of the appendiceal stump is vital to minimize intraabdominal complications and surgical site infections in laparoscopic appendectomy. There are various techniques for the closure of base of the appendix while performing a laparoscopic appendectomy like endoloop, extracorporeal (Roeder’s knot) or intracorporeal knotting, clips and endo stapler. Objective: To assess the safety and efficacy of nonabsorbable hem-o-lock polymer clips for laparoscopic appendiceal stump closure in acute appendicitis. Methodology: This is a descriptive observational study carried out at Brahmanbaria Medical College Hospital from January 2017 to August 2023. Patients, who underwent laparoscopic appendectomy with nonabsorbable hem-o-lok polymer clips appendiceal stump closure, were included in the study. Data on patients’ demography, intraoperative and postoperative complications, operative time and hospital stay were collected for statistical analysis. Result: A total of 42 patients who underwent laparoscopic appendectomy with nonabsorbable hem-o-lok polymer clips stump closure, were included in this study. Among them 62% were female and 38% male. Mean age was 23±4.042 years. The mean operative time was 38.40±8.709 minutes. Mean hospital stay was 2.5±0.707 days. No major intraoperative and postoperative complications observed. Conclusion: The use of nonabsorbable hem-o-lock polymer clips for the closure of appendiceal stump in laparoscopic appendectomy is feasible, safe, fast and effective technique. Due to simplicity of the technique it may be a useful alternative to the other methods of laparoscopic appendiceal stump closure. J Bangladesh Coll Phys Surg 2026; 44: 33-39